Efficacy and Safety of Pravastatin in Placental-Related Disorders: Systematic Review And Meta-Analysis Of Randomized Controlled Trials: english - Saputra, Gede Ardi; Pandiangan, Asri; Suryatman, Muhammad Villiandy; Swastini, Ni Putu (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2025)
Placental-related disorders impact over 33% of pregnancies. Several of these syndromes lead to higher rates of maternal and fetal death and morbidity and can have long-term health consequences. Several RCTs have found that pravastatin is associated with a significant reduction in the incidence of preterm preeclampsia and preterm birth. However, alternatives require substantial evidence. On the methods, two writers assessed the risk of bias. The Cochran test was used to assess heterogeneity among studies. The Mantel-Haenszel technique was used to obtain the results. The study's results were described using forest plots. The study used six randomized controlled trials. Findings showed a reduced risk of preeclampsia, preterm birth, and NICU admission in pregnant women taking pravastatin. There was no significant reduction in the risk of neonatal respiratory distress, congenital disorders, and adverse events of headache, heartburn, and musculoskeletal pain. Our conclusion, this study suggests that pravastatin use may have beneficial effects in reducing the risk of placental-related disorders in patients.